Efficacy of yoga for chronic back pain: A comprehensive meta-analysis of clinical trials - M. D. Sangeetha; B. N. Sharath; P. Seema; P. K. Sreenath Menon; M. Shashi Kumar; M. Sathiabalan; R. Nandhini (Yoga-Mimamsa)
Chronic back pain (CBP) is a significant global health concern associated with substantial disability and economic burden. Yoga has gained attention as a potential intervention for CBP due to its holistic approach to health and well-being. This study aimed to comprehensively assess the efficacy of yoga for CBP through a meta-analysis of clinical trials. A systematic review and meta-analysis were conducted following the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Electronic searches were performed in PubMed from January 2013 to May 2023. Studies that investigated the effects of yoga as an intervention for CBP in adults were included. The risk of bias was assessed using the RoB 2 tool. Pooled mean differences (MDs) with 95% confidence intervals (CIs) were calculated for pain reduction using a random-effects model. Subgroup analyses were conducted based on geographic location, type of intervention, and type of yoga. A total of six randomized controlled trials met the inclusion criteria and were included in the meta-analysis. The analysis demonstrated a significant reduction in pain intensity among participants practicing yoga compared to nonintervention groups (pooled MD = −1.24, 95% CI = −2.28 to − 0.20, p < 0.05). Subgroup analyses revealed variations in pain reduction across different geographical locations, types of interventions, and types of yoga. The findings of this meta-analysis suggest that yoga may be effective in reducing CBP in adults. However, the observed heterogeneity and potential publication bias indicate the need for cautious interpretation.